PEMANFAATAN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L) DAN RUMPUT LAUT (Euchema cottoni) TERHADAP MUTU PERMEN JELLY - Robby Rahadian; Noviar Harun2; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The study was purposed to get the best combination of rosella flower petals (Hibiscus sabdariffa L.) and seaweed (Euchema cottoni).  The research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications. The treatments were rosella flower petals 90% : seaweed 10%, rosella flower petals 80% : seaweed 20%, rosella flower petals 70% : seaweed 30%, rosella flower petals 60% : seaweed 40%, and rosella flower petals 50% : seaweed 50%.  The data obtained were analyzed statistically using Anova and DNMRT at 5%.  The research showed that rosella flower petals and seaweed significant on water content, ash content, degree of acidity (pH), reducing sugar, and sensory evaluation for descriptif and hedonic test. The best treatment of jelly bean from this research was rosella flower petals 60% and seaweed 40% which have water content 16,59%, ash content 0,24%, degree of acidity (pH) 5,81, reducing sugar 23,14%, reddish orange color, a little bit rosella flavour, sweet little sour taste, the texture was little springy and overall assesment of jelly beans was  rather preferred by the panelist’s. Keywords: Jelly beans, rosella flower petals and seaweed.